Effect of physical properties of the liquid on the efficiency of a UV-C treatment in a coiled tube reactor. (May 2015) - Müller, Alexandra; Günthner, Katharina A.; Stahl, Mario R.; Greiner, Ralf; Franz, Charles M.A.P.; Posten, Clemens
Abstract: In liquid foods, various given physical properties affect simultaneously the inactivation of microorganisms by UV-C treatment. Here, the effect of absorption, turbidity and viscosity on the efficiency of UV-C inactivation in a coiled tube reactor was investigated. Model solutions with Escherichia coli DH5α as biodosimeter were chosen. The Weibull fit was suitable to describe the inactivation behavior of E. coli DH5α in the liquids. Regarding the physical parameters, the absorption was identified as the main parameter affecting the inactivation performance. A considerably lower 5 D value was observed for the inactivation kinetic at the highest concentration of cellulose particles compared to the absorptive liquids, indicating a minor effect of turbidity on the reduction rate. However, an underperformance of mixing caused by the high viscosity of 10 mPas was observed in absorptive liquids (40 cm − 1 ). In addition, the inactivation behavior of E. coli DH5α in juices was compared to the reduction in corresponding model juice. It was shown, that inactivation kinetics in model juice can provide first indications for the inactivation behavior of microorganisms in real juices. Industrial relevance: Ultraviolet treatment is a promising non-thermal technology for enhancing shelf life of liquid food, where the various given physical properties affect simultaneously the inactivation of microorganisms. For accurate assessment of process design substantial knowledge of the influencing parameters is required in order to prevent an under- or overestimation of the inactivation efficiency. Highlights: The effect of absorption, turbidity and viscosity on the performance was investigated. The absorption was identified as the main affecting parameter. A minor effect of turbidity on the inactivation efficiency was observed. High viscosities can cause an underperformance in absorptive liquids. Inactivation in model juice provides first indications for the inactivation behavior.